2013
DOI: 10.1101/gad.229518.113
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes engage unique molecular programs to engulf pruned neuronal debris from distinct subsets of neurons

Abstract: Precise neural circuit assembly is achieved by initial overproduction of neurons and synapses, followed by refinement through elimination of exuberant neurons and synapses. Glial cells are the primary cells responsible for clearing neuronal debris, but the cellular and molecular basis of glial pruning is poorly defined. Here we show that Drosophila larval astrocytes transform into phagocytes through activation of a cell-autonomous, steroiddependent program at the initiation of metamorphosis and are the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
207
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(227 citation statements)
references
References 75 publications
9
207
0
Order By: Relevance
“…2) (Awasaki et al 2008;Doherty et al 2009;Muthukumar et al 2014;Stork et al 2014;Tasdemir-Yilmaz and Freeman 2014). Of the three glial subtypes discussed in this chapter astrocytes by far are the most heavily studied.…”
Section: Astrocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…2) (Awasaki et al 2008;Doherty et al 2009;Muthukumar et al 2014;Stork et al 2014;Tasdemir-Yilmaz and Freeman 2014). Of the three glial subtypes discussed in this chapter astrocytes by far are the most heavily studied.…”
Section: Astrocytesmentioning
confidence: 99%
“…However, within 6 h after puparium formation (APF) steroid-dependent signaling events in astrocytes result in their dramatic increase Draper expression, transformation into phagocytes, and initiation of engulfment of pruned axons, dendrites, and synapses (Tasdemir-Yilmaz and Freeman 2014). Blockade of signaling through the ecdysone receptor, or Draper, suppresses axon clearance of MB g neurons (Hakim et al 2014;Tasdemir-Yilmaz and Freeman 2014). Surprisingly, careful genetic studies reveal that there is not a single engulfment pathway responsible for clearance of all neurite debris during pruning.…”
Section: Cns Gliamentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicate that microglia play a major role in synaptic pruning of neurons, and we are only starting to understand the detailed mechanisms of this process. More research is needed to further elucidate the role of the synaptic pruning performed by microglial cells compared with synaptic pruning seen in other glial cells such as astrocytes and self-pruning of neurons (70)(71)(72)(73).…”
Section: Physiological Function Of Microglia In the Adult Brainmentioning
confidence: 99%
“…A Wallerian degeneration process has recently been well exemplifi ed in Drosophila olfactory receptor neurons [79] and it has been shown that draper expression is similarly upregulated when axons undergo injury in this model [79][80][81][82] . Yet, unlike γ-axon pruning where astrocyte-like glia are the major subtype responsible [75,83] , ensheathing glia have been shown to engulf debris during axon injury of olfactory receptor neurons [84] (Fig. 4B).…”
Section: Mediated By Gliamentioning
confidence: 99%